2018
DOI: 10.1177/0269215518818224
|View full text |Cite
|
Sign up to set email alerts
|

Goal-setting in geriatric rehabilitation: a systematic review and meta-analysis

Abstract: Objective:To explore the effect of goal-setting on physical functioning, quality of life and duration of rehabilitation in geriatric rehabilitation compared to care as usual.Data sources:Medline, Embase, CINAHL, PsycINFO and the Cochrane Library were searched from initiation to October 2018.Methods:We included randomized controlled trials (RCTs), controlled before–after studies and studies using historic controls of older patients (mean age ⩾55 years) receiving rehabilitation for acquired disabilities. Our pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Next to the scoring instrument debate, little evidence exists about the feasibility [18] and effects of goal setting with frail older adults [19]. Within this population, very heterogeneous needs and goals can exist [20].…”
Section: Introductionmentioning
confidence: 99%
“…Next to the scoring instrument debate, little evidence exists about the feasibility [18] and effects of goal setting with frail older adults [19]. Within this population, very heterogeneous needs and goals can exist [20].…”
Section: Introductionmentioning
confidence: 99%
“…The goal-setting and health contract program had a small effect size of 0.35. The effect size from a previous study [51] on physical functioning and quality of life was small and significant at 0.11 and 0.09, respectively. As both studies reported small effect sizes, further meta-analysis on these programs is warranted.…”
Section: Discussionmentioning
confidence: 62%
“…Goal setting is a fundamental component of any care plan (Vaughn et al, 2016). Goal setting allows patients to identify the short-and long-term objectives to achieve, taking into account the patient's needs and lifestyle (Wade, 2009;Levack et al, 2015;Smit et al, 2019). Biases and, in particular, the tendency to focus on the negative factors may lead the patients to formulate goals to avoid the negative symptoms (e.g., pain), instead of pursuing the long-term personal growth objectives (e.g., "I will not participate in the intervention because it's tiring: I just need to rest").…”
Section: The Influence Of Biases On the Patients' Decision Makingmentioning
confidence: 99%